Decorticated and non-decorticated BARI lentil varieties: An ample source of essential nutrients, minerals and bioactive compounds - Mohammad Mainuddin Molla; Md. Hafizul Haque Khan; Biddut Chandra Dey; Ashfak Ahmed Sabuz; Md. Golam Ferdous Chowdhury; Md. Shahinuzzaman; Anjumanara Khatun; Md. Abdus Salam; A.B.M. Khaldun; Pankaj Bhowmik; Rajib Podder (Food Chemistry Advances)
BARI lentils play an important role in Bangladesh for providing essential nutrients to combat micronutrient malnutrition. Hence, the objective of the study was to explore the nutritional, mineral, and bioactive compounds analysis of the selected varieties under different milling conditions. Results exhibited that a significant number of bioactive compounds such as ascorbic acid (15.29 mg/100 g), ß-carotene (142.16 mg/100 g), total carotenoid (67.49 mg/100 g), anthocyanin (1.35 mg/100 g), and total phenolic compounds (20.72 mg GAE/100 g) were plentiful in non-decorticated lentil. In contrast, the non-significant amount of ascorbic acid (4.52 mg/100 g), ß-carotene (64.65 mg/100 g), total carotenoid (11.65 mg/100 g), anthocyanin (0.65 mg/100 g), and total phenolic compounds (11.68 mg GAE/100 g) was found in decorticated lentils. Non-decorticated lentils possessed the highest amount of crude protein (29.63 %), crude fiber (14.12 %), Ca (3.55 %), Mg (1.11 %), Fe (219.00 ppm), and Zn (32.62 ppm). A non-significant difference was noted between cooked decorticated and non-decorticated lentils during organoleptic taste by the sensory evaluators. Apart from this, the most instructive findings are, to utilize non-decorticated lentils that will contribute to minimizing the broken loss (cracked loss) and milling cost of the farmers without any presence of ochratoxin and patulin.